Pengaruh Sistem Informasi Akuntansi, Pengendalian Internal dan Motivasi Kerja terhadap Kinerja Karyawan - Hazinatut Daulah; Suwarno Suwarno (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
The research findings indicate that accounting information systems have a positive impact on employee performance, as evidenced by a P-value of 0.026 (P < 0.05). This suggests that implementing effective information systems can enhance efficiency and productivity. Additionally, internal controls significantly influence employee performance, with a P-value of 0.000 (P < 0.05). These results highlight that robust internal controls create a more structured work environment and help reduce the risk of errors. On the other hand, work motivation does not have a significant effect on performance, with a P-value of 0.239 (P > 0.05). This implies that other factors may play a more dominant role in improving performance compared to intrinsic motivation. Overall, the study concludes that accounting information systems and internal controls have a greater positive impact on employee performance, while the effect of work motivation is more limited.